Reply to the 'Comment on "Polymorphism of levofloxacin: structure, properties and phase transformation"' by Tejender S. Thakur, CrystEngComm, 2020, 22, DOI: ; 10.1039/C9CE01400D. Issue 10 (28th February 2020) - Wei, Ning; Zhang, Mingtao; Chen, Jingtao; Gong, Junbo; Wu, Songgu; Wang, Jingkang; Tang, Weiwei
Abstract : Minor structural differences in molecular conformation were found where the levofloxacin molecule takes a less stable conformer in energy rather than the stable conformer as previously expected. Abstract : Full comparison of the experimentally determined crystal structure of the levofloxacin anhydrous α form from single-crystal X-ray diffraction with all the predicted structures from the CSP approach was supplemented. The previous conclusion in regard to the accuracy of predicted structures by crystal structure prediction (CSP) reported in our article (N. Wei, L. Jia, Z. Shang, J. Gong, S. Wu, J. Wang and W. Tang, CrystEngComm, 2019, 21, 6196–6207) was improved. The comparison results indeed demonstrated great similarities in the space group, unit cell parameters and even crystal packing of the predicted structures at rank 2 in the Z ′ = 1 list to the experimental α form, despite the minor structural differences in the molecular conformation and packing arrangement. It was found that the levofloxacin molecules take a less stable conformer in energy rather than the stable conformer as previously expected.